Efektivitas Penerapan Vidio dan Leaflet terhadap Pengetahuan tentang Personal Hygien pada Keluarga di Tatanan Keluarga - Musdalifah; Febri Sriyanti; Andi Ernawati (Formosa Journal of Multidisciplinary Research, 2022)
The purpose of the study was to determine "Effectiveness of using Video and Leaflets on Knowledge in Families about Personal Hygine in Family Arrangements in 2022. This study used experimental research, namely Quasi Experimental, with "Two group Pretest Posttest" approach, with independent T-Test TEST statistical test. The sampling technique was purposive sampling with a sample of 30 people. The results showed that the p-value (Asymp.Sig.(2-tailed)) was 0.007, where the value was 0.007 <0.005 (α) so that Ho was rejected and Ha was accepted, which means that there is a difference in Health Education about Personal Hygiene Using Video and Media Media. Leaflet on Family Knowledge